The Defence Spending - Growth Nexus In Turkey - Ucan, Okyay; Ozturk, Mutlu Basaran; Akyildiz, Abdulmenaf (European Scientific Journal, ESJ, 2016)
Due to globalization the power balances change in the form of a new world. In order to continue their freedom against inner and outer threats, countries have spent some of their national income to the military defence although their nation’s loss of wealth. Recently, it has been wondered how the portion military defence spending has affected the financial growth. In this research, it will be studied on whether defence spending has a triggering effect on economical development. After dealing with the relationship of defence spending with economic growth on the frame of theory, it is concluded that there has been a two dimensional causality relation between defence spending and growth by analyzing 2006 – 2015 years data in long and short terms.